Synthesis of Dansyl Cyclen and Preliminary Study of Its Fluorescent Properties - La Ode Kadidae; Ruslin Ruslin; Thamrin Azis; La Aba; Laode Abdul Kadir (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
The synthesis of a dansyl cyclen-based compound as a potential chemical sensor has been carried out. The initial study of its fluorescent properties has also been conducted. This study aims to synthesize a cyclen-based compound comprising three identical pendant arms and another different arm carrying a dansyl fluorophore. Producing these heterogenous pendant arms, a-three pendant arm cyclen 9 was reacted with dansyl aziridine 10. The synthesis products were characterized using 1H NMR, 13C NMR, IR, and elemental analysis. In addition, a Fluorescent Spectrophotometer has been used to assess the fluorescent intensity changes of the synthetic ligand in a range of pH 2–13 and when it was titrated with some metal ions. Based on the results of characterization with 13C NMR for compound 2 and additional characterization with IR and elemental analysis for its hydrochloric form 11, it is wisely said that the proposed compound has been successfully synthesized, giving 66% yield as viscous brown oil 2. Moreover, the fluorescent property showed that the higher the pH employed, the higher the fluorescent intensity observed. Meanwhile, the addition of some cationic metals revealed that cadmium (II) gave the highest increase in the fluorescent intensities among other cationic metals.